Studies on the Phytohormone Producing Potential of Agriculturally Beneficial Microbial ABM Isolates from Different Rhizosphere Soils of Sunflower in Tamil Nadu - Sivasakthivelan, P (International Journal of Pharmaceutical & Biological Archive, 2012)
Studies on the Phytohormone Producing Potential of Agriculturally Beneficial Microbial ABM Isolates from Different Rhizosphere Soils of Sunflower in Tamil Nadu